Underactive bladder - an underestimated entity - Spinu Arsenie Dan; Ovidiu Gabriel Bratu; Dragos Radu Marcu; Adina Elena Stanciu; Florentina Gherghiceanu; Florentina Ionita-Radu; Simona Bungau; Ana Maria Alexandra Stanescu; Dan Mischianu (Journal of Mind and Medical Sciences)
Introduction. The concept of underactive bladder is relatively new. Currently there is no generally accepted definition of this pathology. Diagnosis depends on urodynamic findings, and symptoms are usually rare and intricated with the symptoms of other urinary pathology. Matherials and methods. This review examines the current literature on underactive bladder regarding pathology, definition, diagnosis, current guidelines, and any further potential medical developments. Conclusions. Underactive bladder is a poorly understood pathologic condition. Only since 2002 has there been any consensus regarding the definition. The diagnosis relies only on urodynamics; clinical diagnosis is a challenge even for a consultant; and treatment does not seem to alleviate much of the suffering. This disease remains underrecognized and undertreated. More research is needed to identify less invasive diagnosis tools and treatment for this pathology.